2021
DOI: 10.3390/ijerph18073802
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Pilates and Yoga on Health-Promoting Behaviors and Subjective Health Status

Abstract: This study investigates whether Pilates and yoga lead people to adopt generally health-promoting lifestyle elements and feel better about their physical and mental fitness. To this end, we designed an 8 week exercise program of Pilates and yoga reviewed by veteran practitioners and conducted an experimental study through which we collected the data from 90 volunteered adult subjects between ages 30 and 49 (mean age = 35.47), equally represented by women and men without previous experience with Pilates or yoga.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
2
17
1
1
Order By: Relevance
“…Şener et al56 in a study conducted on the symptoms of patients with lymphedema, Clinical Pilates exercises were found to be more effective than standard lymphedema exercises. Lim & Hyun57 found that pilates and yoga helped gain healthpromoting behaviors in participants and formed positive beliefs about subjective health conditions in an experimental study they conducted on a total of 90 adult subjects between the ages of 30 and 49 who participated in an 8-week pilates and yoga exercise program. In a study conducted byLeite et al…”
mentioning
confidence: 99%
“…Şener et al56 in a study conducted on the symptoms of patients with lymphedema, Clinical Pilates exercises were found to be more effective than standard lymphedema exercises. Lim & Hyun57 found that pilates and yoga helped gain healthpromoting behaviors in participants and formed positive beliefs about subjective health conditions in an experimental study they conducted on a total of 90 adult subjects between the ages of 30 and 49 who participated in an 8-week pilates and yoga exercise program. In a study conducted byLeite et al…”
mentioning
confidence: 99%
“…It cannot be a complete approach if Pilates effects excessively depend on each practitioner's skills. This issue can be overcome by establishing legitimate training programs and qualifications [43], but, currently, there are many random and unofficial certificates that can be obtained by attending seminars for a few days. There might be certain benefits with such short and intensive courses, but it may take years of practice before Pilates exercise can be prescribed for vulnerable populations, including late-stage adults.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, yoga could be part of a suite of positive psychology interventions (PPIs) that works with other widely recognized PPIs, such as expressing gratitude (Bono et al, 2020), practising kindness (Hui & Kogan, 2018), and meditating (Galante et al, 2016). With the number of US yoga practitioners rocketing from 20.4 million to 55.1 million between 2012 and 2020 (Zuckerman, 2020), there is an increasing body of research on the benefits of yoga (e.g., Gupta & Maurya, 2020;Lim & Hyun, 2021). However, there were limitations in previous work.…”
Section: Article In Pressmentioning
confidence: 99%